Differential Older Workers’ Experience with Technology-related Changes during the COVID-19 Pandemic - Poli, Arianna; Heuer, Annika; Motel-Klingebiel, Andreas (Nordic Journal of Working Life Studies, 2024)
Many workers, including older ones, experienced changes at work during the COVID-19 pandemic, among which was a sudden increase in the use of digital technologies. This paper aims at understanding older workers’ satisfaction with digital technology-related changes at work during the COVID-19 pandemic in the Nordics. Based on novel survey data collected in Sweden in 2020– 2021, we analyzed the experience with digital technology-related changes at work and modeled the (dis)satisfaction with such changes among older workers (aged 50+). Our findings show that groups of older, less educated, reporting concurrent workload changes and digital technology-related difficulties had an increased likelihood of being dissatisfied with digital technology-related changes at work during the COVID-19 pandemic. The results have implications for the theoretical understanding of late working life and for the redefinition of working life policies and age management strategies in times of work digitalization of work.